Prioritization of Decentralized Renewable Energy Technologies for Rural Areas of Bundelkhand Region, India Using Analytical Hierarchy Process (AHP) - Yadav S.; Srivastava G.; Yadav P.; Giri B.S. (My University, 2025)
Bundelkhand region is located in the central part of India and its rural energy demand depends mainly on the nonrenewable energy resources while renewable energy resources are abundantly available in this region. The utilization of renewable sources is the demand of time because non-renewable energy resources are limited in amount and cause environmental pollution. Energy from decentralized renewable energy technologies can play a major role to fulfill the demand the rural areas. The objective of this research is met by the identification and prioritization of the potential renewable energy technologies for rural areas of this region. Prioritization of decentralized renewable energy technologies for this region is done with the help of Analytical Hierarchy Process (AHP). AHP is one of the most widely used multi-criteria decision-making (MCDM) tool for sustainable energy planning. This research focuses on the decentralized renewable energy technologies namely anaerobic digestion, solar photovoltaic and biomass gasification. Four main criteria categorized as technical, economic, environmental and social are selected for this research. The result of this research shows that solar photovoltaic (0.404943) has gained the highest final ranking followed by anaerobic digestion (0.34407) and biomass gasification (0.25099). The results of this research can play a vital role in sustainable development of this region. AHP model is used first time to prioritize the decentralized renewable energy technologies for rural areas of this region. This research may also show a direction to various stake holders for analyzing rural energy technologies in the most effective and efficient way in their future efforts. © 2020. All Rights Reserved.